2022
DOI: 10.3390/diagnostics12102397
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Predictors and Outcomes after Cardiac Surgery in Children with Congenital Heart Disease: An Observational Cohort Study

Abstract: Acute Kidney Injury (AKI) commonly complicates cardiac surgery in children with congenital heart disease (CHD). In this study we assessed incidence, risk factors, and outcomes of postoperative AKI, while testing the hypothesis that, depending on the underlying diagnosis, there would be significant differences in AKI incidence among different diagnostic groups. We conducted an observational cohort study of children with CHD undergoing cardiac surgery in a single tertiary center between January 2019 and August 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The proportion of AKI found in this study is lower than what was reported by Kourelis et al from Greece. 14 Some researchers have shown that AKI incidence following cardiac repair can vary widely, spanning from 11.5% to 62%. [15][16][17][18] The documented in-hospital mortality related to AKI ranges from 1.1% to 79%.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of AKI found in this study is lower than what was reported by Kourelis et al from Greece. 14 Some researchers have shown that AKI incidence following cardiac repair can vary widely, spanning from 11.5% to 62%. [15][16][17][18] The documented in-hospital mortality related to AKI ranges from 1.1% to 79%.…”
Section: Discussionmentioning
confidence: 99%
“…As an array of cardiovascular developmental deformations, CHD is clinically categorized into > 30 distinct isoforms, encompassing double-outlet right ventricle (DORV) and ventricular septal defect (VSD) [2,[7][8][9][10][11][12][13][14]. Though certain mild/minor forms of CHD may resolve spontaneously [2], severe/complex forms of CHD usually lead to worse quality of life [15][16][17], reduced exercise performance [18][19][20][21], neurodevelopmental delay and structural brain anomaly [22][23][24][25][26], ischemic/thromboembolic stroke [27,28], acute renal injury/chronic kidney disease [29][30][31][32], hepatic fibrosis [33,34], pulmonary dysplasia/ pulmonary arterial hypertension [35][36][37], bacte-Am J Transl Res 2024;16 (5):2034-2048 rial endocarditis [38][39][40][41][42], chronic heart failure [43][44][45], supraventricular/ventricular arrhythmias [46][47]…”
Section: Introductionmentioning
confidence: 99%
“…As a global pediatric concern, congenital heart defects comprise a wide spectrum of cardiovascular developmental defects, which are categorized into >25 distinct clinical subtypes, including tetralogy of Fallot (TOF) (1). Although certain minor congenital heart defects spontaneously resolve, severe congenital heart disease may lead to poor health and quality of life (5)(6)(7)(8), diminished physical exercise capacity (9)(10)(11)(12)(13), impaired neurodevelopment (the most prevalent extracardiac manifestation in patients with a congenital heart defect) and brain damage (14)(15)(16)(17)(18), thromboembolic complications (19)(20)(21), acute renal injury and chronic kidney disease (22)(23)(24), hepatic dysfunction (25), pulmonary arterial hypertension (26)(27)(28), infective endocarditis (29)(30)(31), congestive cardiac failure (32)(33)(34), miscellaneous cardiac dysrhythmia (35)(36)(37) and cardiovascular demise (38)(39)(40). Improvement has been made in cardiovascular surgery and transcatheter interventional treatment, which has allowed >90% of children with congenital heart defects to survive to adulthood; adults living with various congenital heart defects outnumber children affected by congenital heart defects (41)…”
Section: Introductionmentioning
confidence: 99%